Electrochemical Performance Measurements of PBI-Based High-Temperature PEMFCs - Javier Parrondo; Chitturi Venkateswara Rao; Sundara L. Ghatty; B. Rambabu (International Journal of Electrochemistry)
Acid-doped poly(2,2′-m-phenylene-5,5′-bibenzimidazole) membranes have been prepared and used to assemble membrane electrode assemblies (MEAs) with various contents of PBI (1–30 wt.%) in the gas diffusion electrode (GDE). The MEAs were tested in the temperature range of 140∘C–200∘C showing that the PBI content in the electrocatalyst layer influences strongly the electrochemical performance of the fuel cell. The MEAs were assembled using polyphosphoric acid doped PBI membranes having conductivities of 0.1 S cm−1 at 180∘C. The ionic resistance of the cathode decreased from 0.29 to 0.14 Ohm-cm2 (180∘C) when the content of PBI is varied from 1 to 10 wt.%. Similarly, the mass transfer resistance or Warburg impedance increased 2.5 times, reaching values of 6 Ohm-cm2. 5 wt.% PBI-based MEA showed the best performance. The electrochemical impedance measurements were in good agreement with the fuel cell polarization curves obtained, and the optimum performance was obtained when overall resistance was minimal.